CULTURAL TRANSFORMATIONS OF THE CITY IN CONDITIONS OF CORONAVIRUS (COVID-19) PANDEMIC - Kravchenko, Оksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Education History proves, there are many examples of transformations that change cities during epidemics. The aim and the tasks of the study are the cultural and philosophical study of the transformation of the city and the peculiarities of the impact of the pandemic on cultural processes. Research methods are cultural and philosophical analysis, the principle of historicism and sociocultural approach. Research results. The coronavirus has dealt such a severe blow to the way of life in megacities that it is already clear: in the pre-crisis mode cities will no longer be able to exist, they will try to respond to the epidemic threat, make life safe for their residents from repeated COVID-19 outbreaks or new ones. Many museums around the world have been able to implement online solutions to ensure visitor access. Compared to previous years, without a pandemic, online traffic has increased by 40%. Discussion. With the introduction of such technologies, the pandemic has allowed people to touch world cultural sites that were previously inaccessible to them for financial or physical reasons. This is seen as a mutual benefit both for the viewer, who has the opportunity to meet cultural needs and cope with the effects of self-isolation, and for technical companies, which have received a new impetus for development and self-improvement against a sharp increase in demand. Urban infrastructure is also changing amid the pandemic. Conclusion. As a result, there are bicycle paths for moving around the city, regardless of public transport. Bicycle is the cheapest and most effective alternative, and you do not need to change the morphology of the city to make bicycle routes accessible.